Design of a governance model for a specific phase of projects in the refining and petrochemical sector in Cartagena-Colombia (2022)
This document proposes a governance model for one of the most critical phases of the life cycle of the refining and petrochemical sector projects, taking as a reference the best practices from the technical point of view raised by industrial referents worldwide, such as UOP and the PDO and NORSOK, this latest reference of standards and standards in the oil and gas industry worldwide. The most relevant topics will be discussed and recommendations will be made by approaching the local industry. © 2022 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.